Developing soft competencies: Conceptual and terminological support - Kondrateva, Irina G. (Вестник Томского государственного университета)
Modern higher education today is changing its vector for training a graduate who is able to constantly acquire knowledge, be creative, ready to make decisions, and demonstrate wide professional erudition. The essence of soft competencies, theoretical and methodological basis for the development of soft competencies; the levels and the stages of development of soft competencies of bachelor's degree linguistics students when studying at the university are highlighted in the article